PENERAPAN NILAI GOTONG ROYONG BERBASIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA ( P5 ) PADA JENJANG SEKOLAH DASAR - Febri Selamet Riyadi; Harto Nuroso; Retno Suci Handayani; Bagus Ardi Saputra (STKIP Subang, 2024)
This study aims to analyze the value of gotong royong in shaping the character of students. This research is expected to find out the strategies carried out by teachers in the application of the value of mutual cooperation based on the Pancasila Student Profile Strengthening Project (P5) at the elementary school level. In 2023, a descriptive qualitative approach was employed in conducting research at Bendungan Semarang Public Elementary School. The data gathering process encompassed observation, interviews, and documentation. The collected data underwent thorough analysis utilizing interactive techniques, which involved data collection, condensation, presentation, and drawing conclusions based on the evidence gathered. The result of the research shows that the implementation of strengthening the Pancasila student profile has been implemented and implemented properly. based on the problems found, SDN Bendungan Semarang has sought the implementation of the Pancasila Student Profile both in the classroom and in the school environment. Through the P5 action, it can strengthen the character dimensions of the Pancasila Learner Profile in students, especially faith, devotion to God Almighty and noble character, mutual cooperation in the environment, being independent, global diversity, critical reasoning and creativity in dealing with problems.